A study of fears in the Indian setting - GG, Prabhu (Journal of All India Institute of Speech and Hearing, 1972)
Fear Survey Schedules (FSS) have been employed both as research instruments as well as clinical assessment techniques. (Lang and Lazovik, 1963, Wolpe and Lang, 1964, Geer, 1965, Manosovitz and Lanyon, 1965, Rubin, et ah, 1968, Braun and Reynolds, 1969, and Rubin, era/., 1909). Wolpe, et al., (1968, p. 27) point out that it is often astonishing to find out many areas of unadaptive anxiety in an individual which have eluded all other avenues of enquiry, come to light through the FSS. The FSS by Wolpe and Lang (1964) has been used quite often in clinical situations, though Bernstein and Allen (1969) claim that its clinical bias has made it least popular and utilitarian when compared with the other fear survey schedules available.